The impact of amelogenesis imperfecta and support needs of adolescents with AI and their parents: an exploratory study - Sneller, Jennifer; Buchanan, Heather; Parekh, Susan (Wiley, 2014)
BACKGROUND: Amelogenesis imperfecta (AI) is a rare inherited dental defect where enamel does not form properly on the teeth. Research has shown that adolescents with AI may experience adverse psychosocial effects; however the impact on parents has not been explored. AIMS: We aimed to explore: (1) experience and perceptions of AI from both the adolescent and their parent's perspective (2) their views on the usefulness of an online support group (OSG) for patients/parents and the potential salient functions of such a resource. DESIGN: We conducted two focus groups; one for adolescent AI patients and one for their parents. Transcripts were analysed using Thematic Analysis. RESULTS: Three themes emerged from the data: 'Living with AI: Do I look bothered?', 'Need for the 'right' online environment' and 'Support needs: Information and beyond'. CONCLUSIONS: The adolescents did not appear to experience adverse psychosocial effects of having AI, which was contrary to their parents' perceptions. Parents reported some adverse consequences of having a child with AI (e.g., practical challenges). If an OSG was to be developed, it would need to be primarily information based and moderated by an AI specialist. Parents may benefit from additional support beyond that of information, such as emotional and tangible support.